1995
DOI: 10.1248/bpb.18.424
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of the Cytotoxicity of Chloroethylnitrosourea by O6-Arylmethylguanines.

Abstract: It was reported recently that monomeric O6-benzylguanine (1) acts as an alternative substrate for a DNA repair enzyme, O6-alkylguanine-DNA alkyltransferase (AGT), and that therefore pretreatment of cells with 1 induces depletion of AGT resulting in an enhanced cytotoxic response to alkylating antitumor agents. In order to study the interaction of O6-benzylguanine derivatives with AGT and to obtain greater AGT depletion, we synthesized the following O6-arylmethylguanine derivatives and related compounds: O6-(4-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…ACNU was supplied by Sankyo (Tokyo, Japan). 06-Arylmethylguanines employed were Ob-benzylguanine, 06-(4-, 3-, and 2-fluorobenzyl)guanines, 06-(4-, 3-, and 2-trifluoromethylbenzyl)guanines, 06-(4-, 3-, and 2-pyridylmethy1)guanines, and Oh-(2-and 1-naphtylmethyl)guanines, and these were synthesized as described previously (Kohda et al, 1995). Structures and identification numbers of the 06-arylmethylguanine derivatives are shown in Figure 1.…”
Section: Agents and Chemicalsmentioning
confidence: 99%
See 2 more Smart Citations
“…ACNU was supplied by Sankyo (Tokyo, Japan). 06-Arylmethylguanines employed were Ob-benzylguanine, 06-(4-, 3-, and 2-fluorobenzyl)guanines, 06-(4-, 3-, and 2-trifluoromethylbenzyl)guanines, 06-(4-, 3-, and 2-pyridylmethy1)guanines, and Oh-(2-and 1-naphtylmethyl)guanines, and these were synthesized as described previously (Kohda et al, 1995). Structures and identification numbers of the 06-arylmethylguanine derivatives are shown in Figure 1.…”
Section: Agents and Chemicalsmentioning
confidence: 99%
“…Thus, the dose required to inhibit the growth of cells by 50% was expressed as ICso, and the D M F was calculated as the ratio of ICso of cells treated with ACNU alone versus the ICso of cells that were treated with 06-arylmethylguanines and subsequent ACNU. Results have been reported (Kohda et al, 1995) and some of them are quoted in Table 11.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…1) used in the present study has been reported previously (24). Briefly, a mixture of a tert-BuOH solution containing Na, a fluorobenzyl alcohol (4-fluorobenzyl alcohol, 3-fluorobenzyl alcohol, or 2-fluorobenzyl alcohol), and 2-amino-6-chloropurine, was heated and then evaporated to remove the tert-BuOH.…”
Section: Chemicalsmentioning
confidence: 99%
“…20 However, these three classes of inhibitors are not ready for in vivo studies, since it is difficult to make BG derivatives labeled at the 8-position; the toxicity of O 6 -(hetarylmethyl)guanines remains to be investigated; and BP derivatives are not as effective as O 6 -BG in mouse liver or spleen due to their short half-life in vivo. 21 The potentiation effect order of the substituted O 6 -BG analogs is para > meta > ortho, 22,23 most likely because the steric effect at the ortho-position plays a more important role than the electronic effect. Preliminary findings from the biological assay of unlabeled 1a, 1b, and 1c warrant further evaluation of radiolabeled 1a, 1b, and 1c as new potential PET tumor imaging agents for the AGT in vivo.…”
Section: Introductionmentioning
confidence: 99%